PENGARUH MODEL PEMBELAJARAN MEA (MEANS-ENDS ANALYSIS) TERHADAP HASIL EKONOMI SISWA - Zainal, Vetri Yanti; Arga, Kharisma Idola (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The problem in the subject of Economics that the authors encountered at SMK Muhammadiyah 2 Bandar Lampung is that there are still many students whose learning outcomes in Economics have not been maximized and have not yet reached the Minimum Mastery Criteria (KKM 70). One of the factors causing the lack of success in learning economics at SMK Muhammadiyah 2 Bandar Lampung due to the activeness of students in receiving subject matter is not good because students only sit quietly, take notes and only the majority of students who pay attention to the teacher explain. The main factor of the problem is when it is still not known with certainty, but from the temporary assumption that the learning method used by the teacher is known to increase student interest in learning and tends to be less effective. The purpose of this research is to find out the effect of the MEA (Means-Ends Analysis) learning model on economic learning outcomes of class X odd semester students of SMK Muhammadiyah 2 Bandar Lampung in the academic year 2017/2018. This study authors use the Experiment method to improve student learning outcomes in Economics. The population is 120 students consisting of 3 classes. Sample class X Accounting as an experimental class and class X Banking as a control class, each numbering 40 students. Samples in the experimental class were taken using the Cluster Random Sampling technique. To test the above hypothesis the writer will use the ttest formula. The results of the calculation of thit 7.46> tdaf 2.00 with a significance level of 0.05. This shows that the test results are quite meaningful and can accept the provisional allegation that using the MEA (Means-Ends Analysis) learning model will have a positive effect on the economic learning outcomes of Grade X SMK Muhammadiyah 2 Bandar Lampung Academic Year 2017/2018, average results learning Economics students using the MEA learning model (Means-Ends Analysis) higher 73.4 than the average learning outcomes of students Economics using conventional learning is 55.7, which means this shows that learning using the AEC learning model (Means- Ends Analysis) is higher than conventional learning.